2018
DOI: 10.1111/cas.13514
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA signatures and metabolomics have high diagnostic value in colorectal cancer using two novel methods

Abstract: Recently, many new diagnostic biomarkers have been developed for colorectal cancer. We chose 2 methods with high diagnostic efficiency, the detection of serum microRNA and metabolomics based on gas chromatography/mass spectrometry (GC/MS), and aimed to establish appropriate models. We reviewed the diagnostic value of all microRNA identified by previous diagnostic tests. We selected appropriate microRNA to validate their diagnostic efficiency, and determined the optimal combination. We included 85 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…[19][20][21] Among the single diagnostic biomarkers of CRC, miR-139-3p has the highest AUROC (0.994). 22,23 MiR-338-5p has been reported to be dysregulated in several cancers. [9][10][11] Using miRNA microarrays, researchers have found that miR-338-5p is upregulated in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Among the single diagnostic biomarkers of CRC, miR-139-3p has the highest AUROC (0.994). 22,23 MiR-338-5p has been reported to be dysregulated in several cancers. [9][10][11] Using miRNA microarrays, researchers have found that miR-338-5p is upregulated in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of short (18)(19)(20)(21)(22)(23)(24)(25) nucleotides) single-strand, non-coding RNA molecules that are evolutionarily conserved across species and regulate gene expression at a post-transcriptional level. 4 MiRNAs play important roles in multiple biological processes, including cell development, proliferation, differentiation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation was that the overall survival of colorectal cancer patients in our hospital is relatively higher when compared with the national data. 13,14 This can be attributed to two reasons. First, our hospital is one of the leading cancer hospitals in China, the standard of care and the competence of our physicians can be assured.…”
Section: Discussionmentioning
confidence: 99%
“…Using the described searching strategy above, a total of 297 articles were initially retrieved out of the selected databases. After manually screening the titles, abstracts and keywords and then checking the full texts, 9 articles involving 10 studies for individual miR-29 and 5 articles containing 6 studies for miRNA combination markers based on miR-29 that met the inclusion norm were finally selected for the diagnostic meta-analysis while six publications including eight studies evaluating the survival outcome were identified eligible in the prognostic meta-analysis [27][28][29][30][31][32][33][34][35][36][37][38][39]. Moreover, three studies assessed the roles of miR-29 and miRNA combination markers in the recurrence prediction of CRC and one study evaluated the biomarker role in the metastasis prediction in CRC [40][41][42][43].…”
Section: Study Identification and Characteristics Of Included Studiesmentioning
confidence: 99%